Guide to environment safety & health management : developing, implementing, & maintaining a continuous improvement program - Alston, Frances (Industrial engineer); DeKerchove, Emily Millikin (Industrial innovation series., 2016)
Although an integral part of the corporate world, the development and execution of a successful Environmental Safety and Health (ES & H) program in today's profit-driven business climate are challenging and complex. Add to that the scarcity of resources available to assist managers in successfully designing and implementing these programs and you've got a perfect storm of regulatory and contractual agreements imposed on businesses. Guide to Environmental Safety and Health Management: Developing, Implementing, and Maintaining a Continuous Improvement Program guides you through the challenges of developing and maintaining an effective ES & H program for any organization. Giving you practical, from-the-trenches knowledge, the book outlines techniques and provides guidance for addressing the challenges involved in setting up ES & H programs. It shows you how your ES & H program can ensure regulatory compliance and contribute to the success of your company both monetarily as well as in shaping public perception. --Cover.